Antecendents of Costumer's Purchasing decisions on Halal Cosmetics in Indonesia - Kartika, Chandra Bella; Santoso, Adi; Kristiyana, Naning (Jurnal Ilmiah Ekonomi Islam, 2023)
The aim of this study was to assess the impact of attitudes, religiosity, knowledge, and environment on purchasing decisions for halal cosmetic products in Indonesia. The participants of this study are Indonesians who purchase halal cosmetic products. The number of samples collected in this study were 200 respondents. The method of determining respondents used a non-probability sampling method in the manner of accidental sampling. The kind of data used in this study is primary data obtained using the online questionnaire method using Google Forms. The method of analysis of this research is SEM with AMOS software tools. According to the findings of this study, attitudes have a significant positive impact on the decision to purchase halal cosmetics in Indonesian adolescents. Meanwhile, Religiosity, Knowledge and Environment have no discernible impact on the purchasing decision halal cosmetics for Indonesian teenager. The limitations of this study are that there are 4 independent variables used and only 1 variable that influences purchasing decisions. This study the data generated was only based on a questionnaire based on perceptions of respondents' answers via Google Froms so that conclusions could be drawn from the data collected through dissemination via Google Forms without direct interviews and observation with the parties involved.